Cultivation of Jatropha curcas (Ratanjot) in Madhya Pradesh, India - Pandey, A.K.; Kumari, Preetesh; Mandal, A.K. (Indian Journal of Agroforestry, 2020)
The country has nearly 63 million hectares of wasteland, out of which 33 million hectares of wasteland have been allotted for tree plantation. Jatropha curcas L. a promising non-edible oil seed, being hardy in nature can survive in harsh soil and climatic conditions and is a suitable species for wastelands and marginal farm lands. It grows widely in Madhya Pradesh as live fence on the boundaries of fields. To augment the supply of non-edible oils for industrial uses efforts were made to promote this species as a plantation crop among the farmers in Madhya Pradesh through public, cooperative and corporate sectors. It was found that though the crop has shown a promise at experimental farm. Being a new crop, it warranted more intensive follow up by the researchers. Nevertheless it is potential source of non-edible oil and needs to be promoted for wastelands development. There is urgent need to evolve cultivation practices under irrigated and rain fed conditions of Madhya Pradesh. In this direction, studies were initiated to standardize cultivation practices of J. curcas for tropical climatic conditions of Madhya Pradesh. Preliminary findings of the study indicate that the crop can be raised by planting polypotted/bare-rooted seedlings/sowing of seeds directly in the field. However, polypotted seedlings planted on ridges in the month of July performed better.